Kualitas pelayanan kesehatan rawat jalan dengan tingkat kepatuhan minum obat penderita tuberkulosis paru - Ahmad Gunawan; Muhammad Arifki Zainaro (Holistik Jurnal Kesehatan, 2020)
Adherence to anti-tuberculosis treatment and  quality of outpatient health servicesBackground: The were 23 lung tuberculosis patients registered at Sragi Health Center. Actually, the Case Detection Rate of Tuberculosis in Lampung Selatan Regency was 60%, below the 70% national target. How ever, specifically in some health centers in the regency, there were some health centers which Case Detection Rate (CDR) is higher than national achievement like Bakauheni Health Center (116%) while the lowest CDR found at Bumidaya Health Center. In this study, Sragi Health Center obtained 41% placing the fourth lowest achievement. On the following year, 2017, Sragi Health Center’s lung tuberculosis patients increased into 38 resulting the second lowest CDR achieve in Lampung Selatan regency.Purpose: To identify the correlation between empathy of health practitioner and the adherence to anti-tuberculosis treatment.Methods: A quantitative study with cross sectional research approach, by total sampling and population was 49 patients with lung tuberculosis. Study was done on 23 March to 25 July 2019 at Sragi Health Center (Puskesmas). The variables are quality of outpatient health services in domain an empathy and the adherence to anti-tuberculosis treatment.Result: Finding that there were of 29 patients (59,2%) acknowledging the health practitioners having good empathy while the other twenty (40,8%) stating the health practitioners exhibiting poor empathy. There was a correlation between empathy of health practitioners and the adherence of taking medicine on lung tuberculosis patients (p value = 0,009 and OR 6,545).Conclusion: There was a correlation between empathy of health practitioners and the adherence to anti-tuberculosis treatment. The health practitioners especially the nurses should show their empathy to the patients in order to build trust to healthcare.Keywords: Adherence; Anti-Tuberculosis Treatment; Quality; Outpatient Health Services; Empathy Pendahuluan: Puskesmas Sragi sebanyak 23 penderita. CDR (Case Detection Rate) Kabupaten Lampung Selatan tahun 2016 sebesar 60% masih dibawah target nasional sebesar 70%, tetapi bila ditilik terdapat beberapa Puskesmas yang mempunyai capaian nilai CDR diatas nasional seperti Puskesmas RI Bakauheni (116%), sedangkan Puskesmas dengan CDR terendah adalah RI Bumidaya (30%) dan Puskesmas Sragi sebesar 41% merupakan urutan yang ke empat terendah. Tahun 2017 Puskesmas Sragi kembali mengalami peningkatan penderita TB paru menjadi sebanyak 38 orang dengan CDR urutan kedua terendah di Kabupaten Lampung Selatan. Tujuan: Diketahui empati petugas kesehatan dengan kepatuhan minum obat penderita tuberculosis paru. Metode: Penelitian kuantitatif, jenis penelitian crossectional. Populasi penelitian seluruh penderita TB paru, jumlah sampel 49 orang, pengambilan sampel secara total sampling dilakukan di UPT Puskesmas Rawat Inap Sragi Kabupaten Lampung Selatan, tanggal 23 Maret – 25 Juli 2019. Variabel penelitian empatidan kepatuhan minum obat penderita tuberculosis paru. Analisis data secara univariat dan bivariat (chi square).Hasil: Diketahui sebanyak 29 (59,2%) memiliki empati baik dan sebanyak 20 (40,8%) memiliki rasa empati yang buruk. Ada hubungan antara empati petugas kesehatan terhadap kepatuhan minum obat tuberculosis paru(p-value=0,009 dan OR 6,545).Simpulan: Ada hubungan antara empati petugas kesehatan terhadap kepatuhan minum obat tuberculosis paru. Saran: Perawat dan petugas kesehatan supaya bersikap empati agar pasien lebih nyaman dan merasa dilindungi dan dibantu sehingga dapat menciptakan kondisi yang terapeutik. Pasien akan selalu kontrol dan patuh dalam minum obat tuberculosis paru hingga dosisnya sesuai anjuran yang ditetapkan.